First record of the pelagic stingray Pteroplatytrygon violacea (Boneparte, 1832) (Family: Dasyatidae) from the east coast of India - Zacharia, P. U.; Joshi, K. K.; Kandan, P. (Indian Journal of Fisheries, 2011)
Pelagic stingray, Pteroplatytrygon violacea, (Boneparte, 1832) was recorded for the first time from the east coast of India. The female specimen measuring 91 cm in TL was collected from the hooks and line landings from Tuticorin on 9th July 2009. The morphometric measurements of the specimen were compared with the specimens previously recorded from west coast of India and from the North Sea. The present specimen agrees with most of the characters of earlier specimens, but variation was observed in the disc width, disc length, eye length, inter-space first gill slits, snout to cloaca length and cloaca to tail length as compared to the paratypes, which may be variations owing to sex-specific differences. The present specimen might have migrated from the populations available in the equator, along with the monsoon currents.